The Academic Writer: A Brief Guide - EDE Lisa (Bedford, 2007)
Much has changed since the first edition of Lisa Ede's Work in Progress; students need more rigorous help working with sources, creating effective arguments, and addressing the greater demands of academic writing in a digital age. Refocused on the kinds of academic writing students do now, The Academic Writer is a radical revision of Work in Progress. Written in Lisa Ede's accessible, supportive style, The Academic Writer gives students easy-to-use guidelines to make effective choices at each stage of the writing process.